(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The novel "Night. Dream. Death. Stars" by Joyce Carol Oates is a powerful story in which the author uses an allusive way of conveying human relationships. It not only reveals the complexity and versatility of human connections and emotions, but also introduces us to the world of symbols and metaphors that help to realize the deep essence of the characters and their relationships. In this article, we will look at how Joyce Carol Oates uses allusions to convey human relationships in the novel.